Benefits of Regular Physical Activity in Improving Mental Health in Students During the Pandemic - Ramadhan, Gildan (Raudhah Publisher, 2024)
The COVID-19 pandemic has had a significant impact on mental health, particularly among students facing unique pressures such as distance learning, social isolation, and uncertainty about the future. This study explores the benefits of regular physical activity in improving mental health among college students during the pandemic. Using a qualitative approach, this study utilizes literature study methods and library research to analyze existing studies on the relationship between physical activity and mental health. The findings suggest that regular physical activity plays an important role in reducing symptoms of anxiety, depression, and stress, thereby improving overall well-being. Exercise has been shown to release endorphins, improve sleep quality, and improve self-esteem, all of which contribute to better mental health. In addition, physical activity provides a constructive channel for managing stress and a sense of routine and normalcy during times of uncertainty. The study emphasizes the importance of incorporating physical activity into daily routines to reduce the adverse impact of the pandemic on mental health. University administrations and policymakers are encouraged to promote and facilitate access to physical activity opportunities for students. Further research should focus on longitudinal studies to better understand the long-term benefits of physical activity on mental health and identify the specific types of exercise that are most effective. The integration of physical activity in mental health strategies is essential to building a resilient and healthy student population in the face of ongoing global challenges.